TANGGUNG JAWAB HUKUM DIREKSI BANK BUMN ATAS KERUGIAN BANK (Studi atas Putusan Mahkamah Agung RI Nomor: 1144 K/Pid/2006) - Heriyanto; Mustofa (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
In addition to having quite a large authority, the Board of Directors alsohas a large role and responsibility in carrying out the company's visionand mission to personal responsibility, especially in carrying out itsresponsibilities as a director of a BUMN Bank whose capital partly comesfrom state finances that are separated into company assets. In this paper,we will discuss the quality of the roles and responsibilities of directors ofstate-owned banks when the bank suffers losses, the extent of directors'responsibility when the bank suffers a loss. In this discussion the authorsuse a normative juridical approach based on the Law on Banking, SOEs,and companies combined with a judge's decision which is used as a knifefor analyzing the quality of roles and responsibilities of BUMN bankdirectors towards bank losses.